English young learners’ HOTs barriers in learning online with digital storytelling - Handi Pabriana; Anisa Septia Megawati; Jeni (Pelita International Publishing, 2025)
Currently, the advancement of technology in education has accelerated, particularly in teaching methodologies. Online or blended teaching has gained popularity in Indonesia. However, barriers persist in teaching English to young learners online, particularly in promoting Higher Order Thinking Skills (HOTs) through digital storytelling. Consequently, this research aims to investigate the barriers faced by English Young Learners (EYL) in acquiring HOTs through online learning with digital storytelling. This qualitative research design employed with case study design in online classroom observation and interviews as research instruments. The analysis revealed that EYL learners encounter difficulties with teaching instruments, technology issues, their English proficiency, and the implementation process. Therefore, it is advisable for future researchers to prioritize and address these barriers.